PJMHS 2022
DOI: 10.53350/pjmhs2022161121
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Clinical Data & Prevalence of Breast Tumors in South Punjab, Pakistan

Abstract: Background: In Western countries, middle-aged women are more vulnerable to breast cancer. Globally, almost a million new cases were identified in 1998. One in 12 women in England and Wales will get the disease at some point.1 Even 5,000 years after it was first reported, the etiology of breast cancer is still unclear, and effective preventative measures are even further off. Aim: To characterize the varied ways in which breast cancer has presented itself among patients at Bahawal Victoria Hospital in Bahawalpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…In the current study, the mean age at diagnosis was 50.34±12.69 years (range: 21-90 years). This is similar to earlier data from across Pakistan [10][11][12][13] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, the mean age at diagnosis was 50.34±12.69 years (range: 21-90 years). This is similar to earlier data from across Pakistan [10][11][12][13] .…”
Section: Discussionsupporting
confidence: 92%
“…The reason for this distinction may be the presence of certain protective factors in the Pakistani population that were also noted in the current study, including multiparity (70.9%), prolonged lactation for >1 year (42.5%), younger age at birth of the first child, low prevalence of hormone replacement therapy (HRT) and younger age at disease presentation. 2,13,[18][19][20] The current study found 1.7% prevalence of ductal carcinoma in-situ (DCIS) cases which was relatively higher than other studies from Pakistan. 2,14 The data is remarkably lower compared to 51% reported DCIS cases in the US.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation